Comparative studies of novel biooxidation process to low-grade sulphide gold ores. Issue 3 (4th July 2022) - Ahn, Junmo; Wu, Jiajia; Lee, Jaeheon
ABSTRACT: The Sand Farming is one of novel biooxidation processes suitable for sulphide oxidation of low-grade refractory gold ores. It has been previously proven to be feasible and more efficient compared to other conventional sulphide oxidation processes. In this study, the Sand Farming was compared with conventional tank biooxidation to investigate biooxidation behaviors on ores with different mineralogy and compare the ultimate gold recovery. Ore samples were tested for Sand Farming biooxidation. Conventional tank biooxidation was also compared as the baseline. After each biooxidation was completed, cyanidation was conducted for gold extraction. The Sand Farming achieved the gold recovery of 75% from high grade with higher sulphur content sample (Sample A) and 68% from low grade with lower sulphur content sample (Sample B), slightly lower than tank biooxidation of 83% and 85%, respectively. Sand Farming can be an alternative to several sulphide oxidation processes with better overall economics.